2003
DOI: 10.1029/2001jc001220
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and salt balances on Georges Bank February–August 1995

Abstract: Temperature and salinity variability over the crest and southern flank of Georges Bank are investigated using moored observations obtained from February to August 1995 and historical data. There was a large seasonal variation in water temperature, which decreased 1°C–2°C in February to a minimum of 5°C due to surface cooling and wind‐forced cross‐bank advection, and then increased steadily due to surface heating, reaching 10°C (southern flank) to 17°C (crest) in August. The crest warmed more than the southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 31 publications
7
30
0
1
Order By: Relevance
“…[9] The CMO moored array consisted of four sites located on the outer half of the New England continental shelf south of Cape Cod, Massachusetts [Lentz et al, 2003b;Shearman and Lentz, 2003]. A heavily instrumented central site on the 70-m isobath was surrounded by three more lightly instrumented sites, an inshore site 11 km onshore of the central site in 64 m of water, an offshore site 12.5 km offshore of the central site in 86 m of water, and an alongshore site 14.5 km east of the central site in 69 m of water (Figure 1).…”
Section: Moored Array and Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] The CMO moored array consisted of four sites located on the outer half of the New England continental shelf south of Cape Cod, Massachusetts [Lentz et al, 2003b;Shearman and Lentz, 2003]. A heavily instrumented central site on the 70-m isobath was surrounded by three more lightly instrumented sites, an inshore site 11 km onshore of the central site in 64 m of water, an offshore site 12.5 km offshore of the central site in 86 m of water, and an alongshore site 14.5 km east of the central site in 69 m of water (Figure 1).…”
Section: Moored Array and Data Processingmentioning
confidence: 99%
“…Lentz et al [2003b] used a 6-month moored array deployment to examine the heat balance at mid-shelf on the southern flank of Georges Bank, to the northeast of the New England shelf. They found that the seasonal increase in temperature from February to August 1995 was primarily due to surface heating while advective heat fluxes dominated the temperature variability over time scales of days to weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature and salinity of shelf water on Georges Bank and off-bank slope water change seasonally [Flagg, 1987;Wright and Parker, 1976;Lentz et al, 2002]. Temperature and salinity for shelf water are about 5°C and 33.2 (1026.25 kg/m 3 in density) and for upper slope water about 10°C and 35 (1026.95 kg/m 3 ) in winter, whereas they are about 15°C and 33 (1024.43 kg/m 3 ) and about 21°C and 35 (1024.50 kg/m 3 ) in summer, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A coerência entre o transporte de Ekman calculado pela tensão de cisalhamento do vento e a temperatura de fundo em diversos sistemas costeiros foi observada por autores como de Szoeke e Richman (1984), Mitchum e Clarke (1986), Lentz (1995Lentz ( , 2001), Samelson (1997), Austin e Lentz (2002). Austin e Barth (2002) O vento de nordeste pode gerar dois tipos de ressurgência, uma ressurgência local devido ao transporte de Ekman, e outra remota, provocada pelo transporte barotrópico de águas ressurgidas ao longo da costa.…”
Section: Discussão Influência Do Campo De Ventosunclassified